Doing Well by Making Well: The Impact of Corporate Wellness Programs on Employee Productivity - Gubler, Timothy; Larkin, Ian; Pierce, Lamar (Management science, 2018)
This paper investigates the impact of a corporate wellness program on worker productivity using a panel of objective health and productivity data from 111 workers in five laundry plants. Although almost 90% of companies use wellness programs, existing research has focused on cost savings from insurance and absenteeism. We find productivity improvements based both on program participation and postprogram health changes. Sick and healthy individuals who improved their health increased productivity by about 10%, with surveys indicating sources in improved diet and exercise. Although the small worker sample limits both estimate precision and our ability to isolate mechanisms behind this increase, we argue that our results are consistent with improved worker motivation and capability. The study suggests that firms can increase operational productivity through socially responsible health policies that improve both workers’ wellness and economic value, and provides a template for future large-scale studies of health and productivity. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2883 . This paper was accepted by Serguei Netessine, operations management.